2006
DOI: 10.1677/joe.1.06679
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal influences on leptin sensitivity and susceptibility to diet-induced obesity

Abstract: Obesity and type 2 diabetes are world wide health issues and their incidence is rapidly increasing. Currently the biological factors responsible for the development of obesity are only partially understood. Recent research has shown that maternal nutrition during pregnancy may have long-term metabolic consequences in offspring. In the present study we investigated interactions between prenatal and postnatal nutrition on leptin sensitivity and obesity development. Wistar rats were time-mated and randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 43 publications
4
72
1
1
Order By: Relevance
“…Our present findings also suggest that exposure to prenatal undernutrition results in adult dysregulation of appetite homeostasis and reduced AgRP mRNA expression, possibly via central leptin resistance, which we have previously shown can occur in the absence of obesity and hyperleptinaemia and is associated with increased plasma C-peptide and triglyceride levels (Krechowec et al 2006). We have also demonstrated that, while exposure to prenatal undernutrition can increase food intake, the development of amplified obesity characterised by excessive fat mass accrual requires a critical interaction with postnatal high-fat nutrition.…”
Section: Discussionsupporting
confidence: 79%
“…Our present findings also suggest that exposure to prenatal undernutrition results in adult dysregulation of appetite homeostasis and reduced AgRP mRNA expression, possibly via central leptin resistance, which we have previously shown can occur in the absence of obesity and hyperleptinaemia and is associated with increased plasma C-peptide and triglyceride levels (Krechowec et al 2006). We have also demonstrated that, while exposure to prenatal undernutrition can increase food intake, the development of amplified obesity characterised by excessive fat mass accrual requires a critical interaction with postnatal high-fat nutrition.…”
Section: Discussionsupporting
confidence: 79%
“…31,33,34,[36][37][38][39][40] Although we did not have data regarding maternal obesity during pregnancy, the odds favouring overweight in children with increasing weight gained during pregnancy was adjusted for the current maternal BMI. As in other studies, [41][42][43][44] we used self-reported height and weight in order to categorize parental BMI, although this measures might not be extremely reliable, because of the low sensitivity of this method to evaluate the prevalence of overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies have indeed demonstrated that infants born small for gestational age are more prone to develop obesity, hypertension and type 2 diabetes in adulthood. [27][28][29] Experimental studies have further corroborated that rodents and other animal species submitted to protein or calorie restriction during gestation and/or suckling exhibit hyperphagia, [30][31][32][33] insulin resistance, 34,35 reduced leptin sensitivity, 36,37 hepatic steatosis, 38 elevated blood pressure 39,40 and hyperlipidemia. 35,37,38 These observations have been explained by the thrifty phenotype hypothesis, also called metabolic programming or the developmental origins of disease.…”
Section: Introductionmentioning
confidence: 93%